(untitled) (Journal of the College of Education for Women, 2019)
Environment suffered in recent years a large corrupting by human; and because of his ignorance of the dimensions of Caliphate in the ground and ignore what it means gearing. The gearing is that the son of Adam, which will benefit the board of Allah Almighty to him in the land of the causes of life, without exaggeration or negligence and without prejudice to the cosmic Balnoames enacted by the Almighty Creator, has urged verses of the Quran Muslim to preserve and protect the environment which is a religious duty, as it showed a great verses he is the author and the splendor and beauty of workmanship and manufacturer greatness of the Almighty, who created all things beautiful.Koran played a major role in the consolidation of environmental education by directing Muslims and groomed behavior to preserve the environment, and the development of environmental awareness in humans by providing it with the right vision for the environment and the behavior towards the study and conservation in order to achieve his role required in the earth as an heir of God in them. The importance of the environment and preservation of the core teachings of the religion that anthropology prevent his brother from marring the terrestrial environment and the marine environment, and that corruption was the result of the wrong people for environmental activities, even if we look at scripture, we find that Islam is a religion preservation of the environment and take advantage of them without harm, including . Required to be at the forefront of environmental education priorities quality stakeholders in order to better human rights and reverse the real photos civilization of Islam.